Centro de Referência do Idoso de Guarulhos: um estudo de caso - Pinto, Maria de Fátima Caetano (2012)
The purpose of this work is a case study on the Reference Centre of the Elderly of the City of Guarulhos (GRCE). Initially, we did a reflection on the concept of the old age and the possibility of understanding it in the medical view. We analyze the assumptions of Social Gerontology, seeing how some authors like, Canguilhem, Messy, Beauvoir, Ayres, and others, propose a new look for sickness and old age. By analyzing public policies on aging, we list a number of benefits and needs of the elderly. Measurements of the UN and WHO are the bases for the construction of a law aimed at the elderly in Brazil. The Elderly Statute, the LOAS and others achievements based managements and services offered by GRCE. The Brazilian Institute of Geography and Statistics (IBGE) data give the size of demand and instability in the senior care. The GRCE was the space of field research that began with a review of documents, went through a description of services and facilities and ended interviews with managers and users. Besides pointing out some difficulties, this study suggests a further use of the GRCE and services to serve, in fact, as a reference for the establishment of others institutions of conviviality and sociability for the elderly